The added value of inclusive research - Walmsley, Jan; Strnadová, Iva; Johnson, Kelley (Journal of applied research in intellectual disabilities, 2018)
Background The study asks when does inclusive research add value? The authors argue that this is important, given the additional time and cost of co‐researching with people with intellectual disabilities. The study is situated in debates about a “second generation” of inclusive research which advocates focussing more on outcomes than process. The authors argue that this is premature, rather the authors propose that inclusive research is valuable when it helps to recognize, foster, and above all communicate the contributions people with intellectual disabilities can make. Method The authors conducted a literature review of 52 peer‐reviewed journal articles about inclusive research and analysed them.. Results The authors conclude that inclusive research adds value when there is a distinctive contribution which only co‐researchers with intellectual disabilities can make, when it highlights the contributions people with intellectual disabilities make, and when it contributes to better lives for the wider population of people with intellectual disabilities. Conclusions The authors propose a revised definition of inclusive research to replace that published by Walmsley and Johnson in 2003.